2005
DOI: 10.1044/1059-0889(2005/009)
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Hearing Aid Orientation Content by First-Time Users

Abstract: On average, participants recognized approximately 75% of the HAO content, which is encouraging from a clinical standpoint, providing support for the efficacy of the HAO and the time audiologists spend in completing it. Moreover, recognition of HAO content improved when tested at 1 month, suggesting audiologists may expect their patients to be aware of a majority of hearing aid use and care information following the hearing aid trial period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 15 publications
3
25
0
4
Order By: Relevance
“…These pieces of information corroborate with the results obtained and discussed before, regarding the users´ performance in the use, manipulation and cleaning of the HA/earmold. Another fact that confirms the results found by the studies mentioned (7,10,12,26) is what two participants reported about not knowing the meaning of the "beep" until watching the DVD and what other two participants reported, pointing the "cotton bud" as the correct way of dealing with the excess of wax in the external auditory canal, also mentioning, that the DVD had such information and emphasized the importance of looking for a otorhinolaryngologist to solve this problem.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…These pieces of information corroborate with the results obtained and discussed before, regarding the users´ performance in the use, manipulation and cleaning of the HA/earmold. Another fact that confirms the results found by the studies mentioned (7,10,12,26) is what two participants reported about not knowing the meaning of the "beep" until watching the DVD and what other two participants reported, pointing the "cotton bud" as the correct way of dealing with the excess of wax in the external auditory canal, also mentioning, that the DVD had such information and emphasized the importance of looking for a otorhinolaryngologist to solve this problem.…”
Section: Discussionsupporting
confidence: 75%
“…Although, literature mentions that besides the level of information retained by the individuals, in the guidance process, be low compared with the level of information provided (10,12,26) , a lot of information is remembered incorrectly (7) . These pieces of information corroborate with the results obtained and discussed before, regarding the users´ performance in the use, manipulation and cleaning of the HA/earmold.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations